Apical Trafficking Pathways of Influenza A Virus HA and NA via Rab17- and Rab23-Positive Compartments - Sato, Ryota; Okura, Takashi; Kawahara, Madoka; Takizawa, Naoki; Momose, Fumitaka; Morikawa, Yuko (Frontiers in Microbiology, 2019)
The envelope proteins of influenza A virus, hemagglutinin (HA) and neuraminidase (NA), play critical roles in viral entry to host cells and release from the cells, respectively. After protein synthesis, they are transported from the trans-Golgi network (TGN) to the apical plasma membrane (PM) and assembled into virus particles. However, the post-TGN transport pathways of HA and NA have not been clarified. Temporal study by confocal microscopy revealed that HA and NA colocalized soon after their synthesis, and relocated together from the TGN to the apical side. Using the Rab family protein, we investigated the post-TGN transport pathways of HA and NA. HA partially colocalized with AcGFP-Rab15, Rab17, and Rab23, but rarely with AcGFP-Rab11. When analyzed in cells stably expressing AcGFP-Rab, HA/NA colocalized with Rab15 and Rab17, markers of apical sorting and recycling endosomes, and later colocalized with Rab23, which distributes to the apical PM and endocytic vesicles. In contrast, HA did not colocalize with AcGFP-Rab8 or Rab10 which mediated biosynthetic secretory/exocytic pathways, especially for basolateral cargos. Overexpression of the dominant-negative (DN) mutants of Rab15 and Rab17, but not Rab23, significantly delayed HA transport to the PM. In contrast, Rab23DN did not severely impair the PM targeting of HA/NA. Live-cell imaging revealed that NA moved rapidly with Rab17 but not with Rab15. NA also moved with Rab23 in the cytoplasm, but this motion was confined at the apical PM. Coimmunoprecipitation indicated that HA was associated with Rab17 and Rab23 in lipid raft fractions. When cholesterol was depleted by methyl-β-cyclodextrin treatment, the motion of NA and Rab17 signals ceased. These results suggest that HA and NA are incorporated into lipid raft microdomains and are cotransported to the PM by Rab17-positive and Rab23-positive vesicles.